Epigenetic mapping of the Arabidopsis metabolome reveals mediators of the epigenotype-phenotype map - Kooke, Rik; Morgado, Lionel; Becker, Frank; van Eekelen, Henriëtte; Hazarika, Rashmi; Zheng, Qunfeng; de Vos, Ric C.H.; Johannes, Frank; Keurentjes, Joost J.B. (Genome Research, 2019)
Identifying the sources of natural variation underlying metabolic differences between plants will enable a better understanding of plant metabolism and provide insights into the regulatory networks that govern plant growth and morphology. So far, however, the contribution of epigenetic variation to metabolic diversity has been largely ignored. In the present study, we utilized a panel of Arabidopsis thaliana epigenetic recombinant inbred lines (epiRILs) to assess the impact of epigenetic variation on the metabolic composition. Thirty epigenetic QTL (QTLepi) were detected, which partly overlap with QTLepi linked to growth and morphology. In an effort to identify causal candidate genes in the QTLepi regions and their putative trans-targets, we performed in silico small RNA and qPCR analyses. Differentially expressed genes were further studied by phenotypic and metabolic analyses of knockout mutants. Three genes were detected that recapitulated the detected QTLepi effects, providing evidence for epigenetic regulation in cis and in trans. These results indicate that epigenetic mechanisms impact metabolic diversity, possibly via small RNAs, and thus aid in further disentangling the complex epigenotype-phenotype map.
10.1101/gr.232371.117